Public Awareness of The Risk Factors for Insect Disease in Koncang Village Pandeglang Banten and Its Review According to Islam Views - putri, firda amanda; Ambar Hardjanti; Firman Arifandi (Junior Medical Journal, 2023)
Introduction: Insects are the dominant group of animals on earth with nearly 80 percent of the total number of species on earth. Of the 751,000 species of insects, around 250,000 species are found in Indonesia. In disease transmission, arthropods can act as vectors that transmit germs or act as intermediate hosts. The purpose of this study was to determine public awareness of the risk factors for disease caused by insects in the Pandeglang community in Koncang Village. Method: This research is a quantitative descriptive study with a cross sectional approach. The population in this study were the people of Koncang Village, Pandeglang Regency, totaling 49 people. The type of data is primary data using a previously prepared questionnaire. The technique used in data analysis is the chi-square test.         Result: The results showed that the level of public knowledge of insect disorder was quite good, the level of community attitude towards insect disorder was good, the level of community behavior towards insect disorder was bad. Based on the results of statistical tests there is no relationship between knowledge and behavior towards insect disease in the community in Koncang Village, Pandeglang Regency, with a p-value of 0.913 (p-value <0.05). There is no relationship between attitudes and behavior towards insect disease in the community in Koncang Village, Pandeglang Regency, with a p-value of 0.819 (p-value> 0.05). Conclusion: There is no statistically significant relationship between knowledge and behavior towards insect pests. There was no statistically significant relationship between attitudes and behavior towards insect pests.